Changes in Pulse Transit Time and Pulse Rate as Markers of Arousal from Sleep in Normal Subjects - Pitson, D.; Chhina, N.; Knijn, S.; van Herwaaden, M.; Stradling, J. (Clinical science (1979), 1994)
1. Obstructive sleep apnoea and its variants often provoke hundreds of short arousals that lead to the most important symptom, disabling hypersomnolence. The measurement of sleep in these conditions requires the documentation of these short arousals and this is conventionally done by manual inspection of the sleeping EEG, a laborious procedure. 2. Other markers of ‘arousal’, that are easier to measure and document, include several cardiovascular signals that change as part of the orienting reflex: pulse rate rise, blood pressure rise, skin vasoconstriction, for example. 3. Pulse transit time (measured as the interval from the ECG R-wave until the arrival of the pulse pressure wave at the periphery, about 250 ms) varies inversely with blood pressure and provides a beat-to-beat estimation of blood pressure changes. 4. In eight normal subjects we have assessed the relationship between transient EEG arousals of different length (provoked by external stimuli) and changes in both pulse transit time and heart rate. 5. Significant falls in pulse transit time occurred in response to external stimuli [15.1 (SEM 1.4) ms], indicating a rise in blood pressure, and were significant even when there was no discernible change in the EEG [9.9 (SEM 2.6) ms]. Significant changes in heart rate also occurred [10.3 (SEM 1.2) beats/min], but were slightly less sensitive than changes in pulse transit time. 6. Changes in pulse transit time (and to a lesser extent pulse rate) are sensitive markers of EEG arousal. As such they should be useful to include when monitoring sleep and its disorders, particularly since pulse transit time recorders can easily be made portable for home use.